Recent Advances in Screening of Anti-Campylobacter Activity in Probiotics for Use in Poultry - Saint-Cyr, Manuel J.; Guyard-Nicodème, Muriel; Messaoudi, Soumaya; Chemaly, Marianne; Cappelier, Jean-Michel; Dousset, Xavier; Haddad, Nabila (Frontiers in Microbiology, 2016)
Campylobacteriosis is the most common cause of bacterial gastroenteritis worldwide. Campylobacter species involved in this infection usually include the thermotolerant species Campylobacter jejuni. The major reservoir for C. jejuni leading to human infections is commercial broiler chickens. Poultry flocks are frequently colonized by C. jejuni without any apparent symptoms. Risk assessment analyses have identified the handling and consumption of poultry meat as one of the most important sources of human campylobacteriosis, so elimination of Campylobacter in the poultry reservoir is a crucial step in the control of this foodborne infection. To date, the use of probiotics has demonstrated promising results to reduce Campylobacter colonization. This review provides recent insights into methods used for probiotic screening to reduce the prevalence and colonization of Campylobacter at the farm level. Different eukaryotic epithelial cell lines are employed to screen probiotics with an anti-Campylobacter activity and yield useful information about the inhibition mechanism involved. These in vitro virulence models involve only human intestinal or cervical cell lines whereas the use of avian cell lines could be a preliminary step to investigate mechanisms of C. jejuni colonization in poultry in the presence of probiotics. In addition, in vivo trials to evaluate the effect of probiotics on Campylobacter colonization are conducted, taking into account the complexity introduced by the host, the feed, and the microbiota. However, the heterogeneity of the protocols used and the short time duration of the experiments lead to results that are difficult to compare and draw conclusions at the slaughter-age of broilers. Nevertheless, the combined approach using complementary in vitro and in vivo tools (cell cultures and animal experiments) leads to a better characterization of probiotic strains and could be employed to assess reduced Campylobacter spp. colonization in chickens if some parameters are optimized.